Analisa Metode VIKOR pada Rekomendasi Alat Musik Keyboard Electone Terbaik - Azi Arisandi; Eka Satria Pribadi (LPPM STIKOM Tunas Bangsa, 2020)
The purpose of this study is to recommend the best electone keyboard. The method used in this research is Visekriterijumsko Kompromisno Rangiranje (VIKOR) Algorithm where the data source used is obtained from the results of questionnaires and interviews. Decision Support System is an alternative to making appropriate and efficient decisions in the process of selecting electune keyboard instruments. The VIKOR algorithm is used to find the best alternative. The alternatives used are Yamaha PSR S970 (A1), Korg PA 50 (A2), Casio MZX (A3), Technis KN 2000 (A4). The results of the study using VIKOR are in the form of ranking, where the first ranking is Yamaha PSR S97 (A1) and the second is Technis KN 2000 (A4).